2016
DOI: 10.1590/1807-1929/agriambi.v20n11p1025-1030
|View full text |Cite
|
Sign up to set email alerts
|

Quality of soybean seeds with high mechanical damage index after processing and storage

Abstract: A B S T R A C TThis study aimed to evaluate the quality of soybean seeds with high level of mechanical damages from different processing stages and stored with and without fungicide treatment. Collections of seed samples were performed during the processing at the following points: hopper, pre-cleaning, dryer, cleaning, spiral, sieve-classifier and the gravity table. The experimental design was completely randomized in a 9 x 2 factorial scheme, with 9 collection points and two seed treatments, in four replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…The accelerated aging test of soybean seeds showed that, after being categorized by the gravimetric table, there was an increase in the percentage of normal seedlings emerged. Such outcome attests the positive effect of the method on the physiological quality of those seeds (Neves et al, 2016). The same, however, did not occur in castor seeds of both genotypes EFV102 and EFV103, as their physiological quality was merely maintained after processing (groups D1 and D2).…”
Section: Genotypementioning
confidence: 64%
See 3 more Smart Citations
“…The accelerated aging test of soybean seeds showed that, after being categorized by the gravimetric table, there was an increase in the percentage of normal seedlings emerged. Such outcome attests the positive effect of the method on the physiological quality of those seeds (Neves et al, 2016). The same, however, did not occur in castor seeds of both genotypes EFV102 and EFV103, as their physiological quality was merely maintained after processing (groups D1 and D2).…”
Section: Genotypementioning
confidence: 64%
“…Seed processing procedures are undeniably relevant to the productive chain, as one of its primary goals is to perfect the quality of the lots, so that the minimum standards for commercialization are met (Baudet et al, 1999;Neves et al, 2016). In this sense, the necessity of keeping the uniformity in water content at safe levels is crucial to prevent seed deterioration, and therefore to assure their storage potential (Antonello et al, 2009;Silva et al, 2010;Silva et al, 2011;Juvino et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Krzyzanowski (1999) state that mainly mechanical damages can occur during processing, which influences the physical and physiological quality of the seeds, since the falls, transport, mats, elevators and other equipment can cause damage to the seeds. Pinto, Mondo, Gomes-Júnior, and Cicero (2012) and Neve et al (2016) argue that mechanical damage is caused by collisions between seeds or on hard surfaces and that such conditions reduce germination and vigour, which may result in a reduction in their sanitary quality. The results of this study converge to suggest that the cracks arising in the seeds come from the transport of seed mass during the drying and later processing, independent of the physical conditions of the air used in the drying process.…”
Section: Asmentioning
confidence: 99%